Advancing Soil Erosion Assessment: Application of Remote Sensing and Geospatial Techniques in Bulango Ulu Reservoir Basin - Olii Muhammad Ramdhan; Kironoto Bambang Agus; Olii Aleks; Pakaya Ririn; Olii Abdul Kadir Zailani (E3S Web of Conferences, 2024)
Soil erosion is an important concern due to the steepness of the terrain and the significant elevation differential between the upstream and downstream regions of the basin. Revised Universal Soil Loss Equation (RUSLE) was integrated with Remote Sensing (RS) and Geographic Information System (GIS) in the current work establish the annual soil erosion map in the Bulango Ulu Reservoir basin. The RUSLE model incorporated soil erosion zonation features such as rainfall erosivity, soil erodibility, topographic, vegetation cover, and conservation support practices. The results show that 0 and 110.31 t year−1 are the minimum and maximum soil erosion, with the average rate of soil erosion is 17.30 t year−1 in the present study area. Soil erosion risk regions were divided into five categories: very slight, slight, moderate, severe and extremely severe soil erosion areal extent and area percentages is 229.17 km2 (94.48%), 7.83 km2 (3.23%), 4.25 km2 (1.75%), 1.20 km2 (0.50%), and 0.12 km2 (0.05%), respectively. The Area Under Curve was indicated that RUSLE model had good performance (75.1%). This study demonstrates the utility of GIS and remote sensing for predicting soil erosion, allowing important information to be extracted for implementing soil conservation programs in the Bulango Ulu reservoir basin.